Photoelectrochemical Polymerization of Thiophene on Self-Assembled RuL2(NCS)(2)/Di(3-Aminopropyl)Viologen on Indium Thin Oxide - Lee, Wonjoo; Hyung, Kyung-Hee; Hwang, Yunhee; Cho, Byung Won; Lee, Soo-Hyoung; Han, Sung-Hwan (AMER SCIENTIFIC PUBLISHERS, 2011)
Polythiophene layers were formed on self-assembled monolayers (SAMs)/indium tin oxide (ITO) using photoelectrochemical polymerization. The SAMs on ITO was prepared using Ru(4,4'-dicarboxylic acid-2,2'-bipyridine)(2)(NCS)(2) and di(3-aminopropyl)viologen. The photoelectrochemically polymerized polythiophene layers on SAMs/ITO were characterized using UV-vis. absorption spectroscopy, atomic force microscopy, scanning electron microscopy, and cyclic voltammetry. The polymer layers have thickness of similar to 360 nm, a dense surface morphology, optical gap of 2.38 eV, highest occupied molecular orbital of -5.2 eV and lowest unoccupied molecular orbital of -2.82 eV. In photoelectrochemical cells, the polythiophene on SAMs/ITO electrode showed a photocurrent of 5 mu A/cm(2).
Keywords: SENSITIZED SOLAR-CELLS; ELECTRICAL-CONDUCTIVITY; PHOTOCURRENT; POLY(3,4-ETHYLENEDIOXYTHIOPHENE); NANOPARTICLES; PERFORMANCE; SYSTEM